PERSEPSI MAHASISWA ANGKATAN 2021 TERHADAP EXTENSIVE READING PADA MATAKULIAH TADOKU 3 - Ridho Khasdullah; Nana Rahayu; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is about a perception students on extensive reading.perception is a Perception is an individual process in interpreting, organizing and giving meaning to stimuli that come from the surrounding environment. The purpose of this study is to see how students perceive. The data was collected from interview students.Key Words: extensive reading, perceptions, tadoku